Diurnal, seasonal, and annual trends in atmospheric CO2 at southwest London during 2000–2012: Wind sector analysis and comparison with Mace Head, Ireland. (March 2015) - Hernández-Paniagua, Iván Y.; Lowry, David; Clemitshaw, Kevin C.; Fisher, Rebecca E.; France, James L.; Lanoisellé, Mathias; Ramonet, Michel; Nisbet, Euan G.
Abstract: In-situ measurements of atmospheric CO2 have been made at Royal Holloway University of London (RHUL) in Egham (EGH), Surrey, UK from 2000 to 2012. The data were linked to the global scale using NOAA-calibrated gases. Measured CO2 varies on time scales that range from minutes to inter-annual and annual cycles. Seasonality and pollution episodes occur each year. Diurnal cycles vary with daylight and temperature, which influence the biological cycle of CO2 and the degree of vertical mixing. Anthropogenic emissions of CO2 dominate the variability during weekdays when transport cycles are greater than at weekends. Seasonal cycles are driven by temporal variations in biological activity and changes in combustion emissions. Maximum mole fractions (μmol/mol) (henceforth referred to by parts per million, ppm) occur in winter, with minima in late summer. The smallest seasonal amplitude observed, peak to trough, was 17.0 ppm CO2 in 2003, whereas the largest amplitude observed was 27.1 ppm CO2 in 2008. Meteorology can strongly modify the CO2 mole fractions at different time scales. Analysis of eight 45° wind sectors shows that the highest CO2 mole fractions were recorded from the E and SE sectors. Lowest mole fractions were observed for air masses from the S and SW. Back-trajectory and meteorological analyses of the data confirm that the dominant sources of CO2 are anthropogenic emissions from London and SE England. The largest annual rate of increase in the annual average of CO2, 3.26 ppm yr −1 ( p  < 0.05), was for the W sector with a smaller increase, 2.56 ppm yr −1 ( p  < 0.05), for the E sector. Calm winds showed an annual growth rate of 1.16 ppm yr −1 CO2 ( p  < 0.05) implying declining local sources. The EGH site shows an average growth rate of 2.5 ppm yr −1 CO2 ( p  < 0.05) over the measured period, which exceeds the observed global trend and contrasts with the decrease in CO2 emissions reported in UK greenhouse gas inventories. This is presumably because the region has had higher growth in combustion emissions than the global average, though the low growth rate in calm weather implies the local emissions have grown more slowly. The seasonal cycle at EGH had larger amplitudes than those recorded at the Mace Head Atmospheric Research Station (MHD) on the W coast of Ireland. Overall, the growth rate observed in annual average CO2 at EGH was larger than that at MHD by about 0.5 ppm yr −1 . Highlights: We analysed ambient data for CO2 recorded in Southwest London during 2000 to 2012. CO2 varied on times scales ranging from minutes to inter-annual and annual cycles. CO2 showed a higher rate of increase than the observed global trend. The greatest concentrations for CO2 were recorded from the E and SE sectors. The CO2 measured at Egham is slightly higher than at Mace Head.